Phylogenetic analysis of Phoma species - Irinyi, László; Kövics, György; Sándor, Erzsébet (Acta Agraria Debreceniensis, 2007)
The cosmopolitan Phoma genus contains mainly phytopathogenic, opportunistic parasites, and saprophyte fungal species. Up to now, the characterization of Phoma species and other taxa of Phoma has been determined on the basis of morphology on standardized media, and gene sequence analysis was only used as a confirmative or distinctive complement. In this study, we tried to find molecular markers which can be used as phylogenetics markers in the molecular based classification in the Phoma genus. We employed a part of the translation elongation factor 1 subunit alpha (EF-1α=tef1) containing both introns and exons and ITS region containing the internal transcribed spacer regions 1 and 2 and the 5.8S rDNA, as potential genetic markers to infer phylogenetic relationships among different Phoma taxa. Twelve different Phoma species sequences were analysed together with the closely related Ascochyta ones. The constructed phylogenetic trees, based on tef1 and ITS sequences, do not support the traditional Phoma sections based on morphological characterization. However, we managed to distinguish between the Phoma strains and Ascochyta species by comparing their tef1 sequences through parsimony analysis. We proved that a tef1 can be a useful phylogenetic marker to resolve phylogenetic relationships at species level in Phoma genus. Both parsimony sequence analyses confirmed that the Phyllosticta sojicola species is identical to the Phoma exigua var. exigua species as Kövics et al. (1999) claimed. However, the evolutionary distance by ITS sequences within Phoma species is too small to get well based consequences for the phylogenetic relationships of Phoma genus. Further investigations would be necessary to clarify whether the tef1 and ITS sequences as phylogenetic molecular markers are well suited for the classification of Phoma species.